2017
DOI: 10.7567/jjap.56.10pf14
|View full text |Cite
|
Sign up to set email alerts
|

Control of La-doped Pb(Zr,Ti)O3crystalline orientation and its influence on the properties of ferroelectric random access memory

Abstract: We investigated the crystallization mechanisms of sputter-deposited La-doped Pb(Zr,Ti)O3 (PLZT) on a Pt/Ti metal stack in the postdeposition annealing (PDA) at 600 °C in O2-mixed Ar ambient. As-deposited amorphous PLZT generally transforms to a perovskite phase over 550 °C through a metastable pyrochlore phase during the PDA. We found that the O2 content of the PDA ambient crucially affects the pyrochlore-perovskite transformation (PPT) speed. While an O2 content much higher than 2% of the PDA ambient suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The lower the XRD intensity, the more highly oriented PLZT is obtained resulting in higher electronic properties of the PLZT capacitor and higher FRAM production yields. The optimum oxygen margin of the PLZT on the BE structure of Pt=AlO x is higher than that on the Pt=Ti BE structure 8,9).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The lower the XRD intensity, the more highly oriented PLZT is obtained resulting in higher electronic properties of the PLZT capacitor and higher FRAM production yields. The optimum oxygen margin of the PLZT on the BE structure of Pt=AlO x is higher than that on the Pt=Ti BE structure 8,9).…”
mentioning
confidence: 83%
“…The optimum oxygen margin of the PLZT on the BE structure of Pt=AlO x is higher than that on the Pt=Ti BE structure. 8,9) XRD intensity, the more highly oriented PLZT is obtained, resulting in better electronic properties of the PLZT capacitor. Although the optimum O 2 content range of PDA was very marginal at around 2% for a Pt=Ti BE, a Pt=AlO x BE was also found to widen the optimum O 2 content range from 2 to 50% as shown in Fig.…”
Section: History Of Fram Development In Fujitsumentioning
confidence: 99%
“…However, material choice of the underlying layer of the Pt BE is presently an important issue to determine FRAM mass producibility, especially its production yield. Although we try to reduce the footprint of the ferroelectric capacitor by employing a TiO x underlying layer (TiO x -UL) of Pt BE instead of our previously used Ti underlying layer (Ti-UL) 12) because we found that polarization of the Ladoped lead zirconate titanate (PLZT) capacitor with TiO x -UL was larger than that of Ti-UL in our experiments. The number of the failed bit in FRAM comprising the PLZT capacitor with TiO x -UL was found to be larger than that of FRAM with ferroelectric capacitor using Ti-UL.…”
Section: Introductionmentioning
confidence: 98%
“…2,11) We have mass-produced FRAM since 1999 and improved its performance including the device reliability though our over 19-year production experiences. 11,12) However, it has relatively larger cell area or unit memory area than other conventional and emerging NVNs mainly due to large ferroelectric capacitor footprint. We tried to reduce the FRAM-cell area by optimizing materials used in ferroelectric capacitors.…”
Section: Introductionmentioning
confidence: 99%
“…An ambient O 2 content of around 2% in PDA results in the growth inhibition of randomly oriented PLZT grains in the perovskite phase near the PLZT surface on the Pt=Ti bottom electrode, which reveals better electrical characteristics and manufacturing yield than in the case of PDA at ambient O 2 contents of higher or lower than 2%. 32) However, the narrow margin of the O 2 content, which effectively suppresses the growth of randomly oriented-PLZT grains, is an issue in the manu-facturing process. In this research, we attempted to develop ferroelectric capacitor fabrication techniques to enlarge the narrow manufacturing process margin and investigate the crystallization mechanisms of PLZT during PDA.…”
Section: Introductionmentioning
confidence: 99%